A Dual-Pathogen Mitral Valve Endocarditis Caused by Coxiella burnetii and Streptococcus gordonii—Which Came First? - Kaemmerer, Ann-Sophie; Ciotola, Francesco; Geißdörfer, Walter; Harig, Frank; Mattner, Jochen; Seitz, Tatjana; Suleiman, Mathieu; Weyand, Michael; Heim, Christian (Pathogens, 2023)
Infective endocarditis (IE) is still a life-threatening disease with high morbidity and mortality. While usually caused by a single bacterium, poly-microbial infective endocarditis (IE) is rare. Here, we report a (blood-culture-negative) dual pathogen mitral valve IE caused by Coxiella burnetii and Streptococcus gordonii: A 53-year-old woman was presented to an internal medicine department with abdominal pain for further evaluation. Within the diagnostic work up, transthoracic echocardiography (TTE) revealed an irregularly shaped echogenic mass (5 × 13 mm) adherent to the edge of the posterior mitral valve leaflet and protruding into the left atrium. As infected endocarditis was suspected, blood cultures were initially obtained, but they remained negative. Chronic Q fever infection was diagnosed using serologic testing. After the occurrence of cerebral thromboembolic events, the patient was admitted for mitral valve surgery. Intraoperatively, a massively destructed mitral valve with adhering vegetations was noted. Examination of the mitral valve by broad-range bacterial polymerase chain reaction (PCR) and amplicon sequencing confirmed Coxiella burnetii infection and yielded Streptococcus gordonii as the second pathogen. Based on the detailed diagnosis, appropriate antibiotic therapy of both pathogens was initiated, and the patient could be discharged uneventfully on the 11th postoperative day after a successful minimal-invasive mitral valve replacement.
CRIS-Team Scopus Importer:2023-10-20
Keywords: blood-culture-negative endocarditis; Coxiella burnetii; dual-pathogen endocarditis; endocarditis; minimally invasive mitral valve replacement; polymicrobial infective endocarditis; Q fever; Streptococcus gordonii

A Practical Approach to Systemic Mastocytosis Complications in Cardiac Surgery: A Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Brückl, Valeska; Fechner, Jörg; Kaemmerer, Ann-Sophie; Wilk, Florian; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2023)
(1) Background: Systemic mastocytosis is a rare, non-curable disease with potential life-threatening complications in patients receiving cardiac surgery. (2) Methods: This systematic review of the literature was prompted by the case of a life-threatening anaphylactic reaction during cardiac surgery related to systemic mastocytosis. The search of all types of studies, using several databases (Pubmed, Scopus and Web of Science), was conducted through September 2022 to identify the relevant studies. (3) Results: Twelve studies were included describing cases of patients undergoing cardiac surgery who were diagnosed with systemic mastocytosis. An adverse effect, namely anaphylaxis, has happened in three cases. Different strategies of premedication, intraoperative and postoperative management were used. In our case, the patient was admitted for elective biological aortic valve replacement due to severe aortic stenosis. Intraoperatively, the patient developed an anaphylactic shock during the administration of protamine after separation from the cardiopulmonary bypass. This anaphylaxis reaction was a complication of the pre-existing systemic mastocytosis and could be successfully managed by the administration of epinephrine, antihistamines and corticosteroids. (4) Conclusions: This systematic literature search and case report highlight the importance of careful preoperative planning, as well as coordination between cardiac surgeons, anesthesiologists and hemato-oncological specialists, in patients with rare but complication-prone diseases such as systemic mastocytosis.
CRIS-Team WoS Importer:2023-03-10

Bioelectrical Impedance Analysis as a Contemporary Biomarker of Obesity in Adults with Marfan- or Loeys-Dietz-Syndrome - Freilinger, Sebastian; Suleiman, Mathieu; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Schopen, Judith; Meierhofer, Christian; Nagdyman, Nicole; Kaemmerer, Harald; Weyand, Michael; et al. (Reviews in Cardiovascular Medicine, 2022)
Background: It is clinically widely overlooked that many patients with Marfan- (MFS) or Loeys-Dietz-Syndrome (LDS) are obese. While anthropometric routine parameters are not very suitable, the modern Bioelectrical Impedance Analysis (BIA) seems superior for the acquisition of reliable noninvasive assessment of body composition of patients. The aim of the study was to assess the body composition of patients with MFS/LDS by BIA in order to detect occult obesity, which may be a risk marker for aortic or vascular complications. Methods: In this exploratory cross-sectional study, 50 patients (66% female; mean age: 37.7 +/- 11.7 [range: 17-64] years) with a molecular genetic (n= 45; 90%) or clinical (n= 5; 10%) proven diagnosis of MFS or LDS were enrolled between June 2020 and February 2022. All BIA-measurements were performed with the Multifrequence-Impedance-Analyzer Nutriguard-MS (Data Input, Poecking, Germany). Results: The MFS/LDS collective was significantly different from an age-, sex-, and BMI-adjusted control in terms of body fat, percent cell ularity, body cell mass, extra cellular mass/body cell mass index, and phase angle (all p < 0.05). The mean I31A-measured bodyfat was 31.7 +/- 8.7% [range: 9.5.-53.5%], while the mean calculated 13MI of the included patients was 23.0 +/- 4.8 kg/m(2) [range: 15.2-41.9 kg/m(2)]. Therefore, using the obesity cut-off values for the body fat percentage of 25% in men and 35% in women, the BIA classifies as many as 28 patients (56.0%) as obese. In contrast only 12 patients (24.0%) were pre-obese, respectively 3 (6.0%) obese by BMI. The significant difference (p < 0.001) had an accordance of 42.7%. Overall, 15 patients (13 MFS; 2 LDS) had previous aortic surgery (n=14) and/or interventional treatment (n=2) for aortic complications (aneurysm, aortic dissection). 11 out of these 15 (73.3%) were currently classified as obese by BIA. Conclusions: The fact that many patients with MFS or LDS are obese is widely unknown, although obesity may be associated with impaired vascular endothelial function and an increased risk of cardiovascular complications. Also, in patients with MFS/I.DS, INA allows a reliable assessment of the body composition beyond the normal anthropometric parameters, such as BMI. In the future, BIA-data possibly may be of particular i mportance for the assessment of the vascular risk of MFS/LDS patients, besides the aortic diameters.
CRIS-Team WoS Importer:2022-07-22

Calcified Amorphous Tumor and Granulomatosis with Polyangiitis—Case Report and Systematic Review of the Literature - Suleiman, Mathieu; Agaimy, Abbas; Dewald, Oliver; Kaemmerer-Suleiman, Ann-Sophie; Mellert, Fritz; Weyand, Michael; Harig, Frank (Journal of Clinical Medicine, 2025)
Background: Calcified amorphous tumor (CAT) is a rare, mostly incidental tumor-like cardiac lesion of unknown histogenesis. Current imaging modalities do not differentiate between CAT and other masses. As it can be a source for embolization, surgical excision of CAT is mandatory. CAT in patients with Granulomatosis with polyangiitis (GPA) is exceedingly rare. Methods: This systematic literature review was prompted by the case of a CAT in a patient with GPA. The search of all types of studies in two databases (PubMed and Scopus) was conducted through November 2024 to identify the relevant studies. Results: Nine studies were included describing cases of patients being diagnosed with GPA and a cardiac mass. All included patients had a histopathological examination of the either biopsied or surgically resected mass. Only one case reported a CAT. In our case, the patient was diagnosed with GPA through a kidney biopsy, whereas a cardiac mass in the right atrium was diagnosed by echocardiography during evaluation for possible kidney transplantation. One year later a progression was observed, and the mass was resected. The histopathological examination revealed a CAT. The patient could be successfully discharged in a good clinical condition. Conclusions: This systematic literature search and case report highlight the importance of regular echocardiographic examination in patients with GPA. Moreover, surgical excision is crucial for the diagnosis and for further therapy planning, regardless of whether the mass is neoplastic or not.
CRIS-Team Scopus Importer:2025-01-31
Keywords: calcified amorphous tumors; cardiac mass; CAT; granulomatosis with polyangiitis (GPA); Wegener’s granulomatosis

Congenital heart disease – don't forget the aorta Angeborene Herzfehler – die Aorta nicht vergessen - Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Meierhofer, C.; Freilinger, S.; Weyand, Michael; Ewert, P.; von Kodolitsch, Y. (Chirurgische Praxis, 2023)
Patients with congenital heart disease (CHD) are considered chronically ill. Despite the growing body of evidence for the relevance of aortic disease in the context of CHD, it is vastly neglected. An aortopathy can have a major negative impact on morbidity and mortality, depending on the underlying heart defect and the patient’s age. Therefore, all affected patients require a life-long follow-up and access to state-of-the art specialized care. Future goals consequently aim to an increased awareness both in caregivers and patients for aortic affections and complications in patients with CHD.
CRIS-Team Scopus Importer:2023-10-20
Keywords: aortic aneurysm; aortic dilatation; aortopathy; congenital heart disease; connective tissue disease; hereditary aortic disease

Continuous Long-Term Assessment of Heart Rate Variability in Adults with Cyanotic Congenital Heart Disease after Surgical Repair - Pieringer, Felix; Suleiman, Mathieu; Kaemmerer-Suleiman, Ann-Sophie; Dewald, Oliver; Freiberger, Annika; Huntgeburth, Michael; Nagdyman, Nicole; Neidenbach, Rhoia; von Scheidt, Fabian; Kaemmerer, Harald; Ewert, Peter; Weyand, Michael; et al. (Journal of Clinical Medicine, 2024)
Background: Heart rate variability (HRV) is an established, non-invasive parameter for the assessment of cardiac autonomic nervous activity and the health status in general cardiology. However, there are few studies on HRV in adults with congenital heart defects (CHDs). The aim of the present study was to evaluate the use of long-term continuous HRV measurement for the assessment of global health status in adults with cyanotic CHD. Methods: This prospective study included 45 adults (40% female, mean age = 35.2 ± 9.2 [range: 19–58] years) after cardiac surgical repair. HRV parameters were calculated from continuous 24 h measurements using a Bittium Faros 180 sensor (Bittium Corp., Oulu, Finland). Results: Postoperative patients with transposition of the great arteries (TGA) (n = 18) achieved significantly higher values of standard deviation of NN intervals (SDNN) (175.4 ± 59.9 ms vs. 133.5 ± 40.6 ms; p = 0.013) compared with patients with other conotruncal anomalies (n = 22). Comparing patients with TGA after a Senning–Brom or Mustard operation (n = 13) with all other heart surgery patients (n = 32), significantly higher HRV parameters were found after atrial switch (root mean square of successive RR interval differences: 53.6 ± 20.7 ms vs. 38.4 ± 18.3 ms; p = 0.019; SDNN: 183.5 ± 58.4 ms vs. 136.3 ± 45.3 ms; p = 0.006). A higher SDNN was also measured after Senning–Brom or Mustard operations than after a Rastelli operations (n = 2) (SDNN: 183.5 ± 58.4 ms vs. 84.5 ± 5.2 ms; p = 0.037). When comparing atrial switch operations (n = 3) with Rastelli operations, the SDNN value was significantly shorter in the Rastelli group (p = 0.004). Conclusions: Our results suggest that continuous HRV monitoring may serve as a marker of cardiac autonomic dysfunction in adults with cyanotic CHD after surgical repair. Impaired cardiac autonomic nervous activity may be associated with an increased risk of adverse reactions in patients with repaired CHD. Therefore, a longitudinal assessment of HRV patterns and trends may provide a deeper insight into dynamic changes in their autonomic regulation and disease progression, lifestyle changes, or treatments. As each person has individual variability in heart rate, HRV may be useful in assessing intra-individual disease progression and may help to improve personalized medicine. Further studies are needed to better understand the underlying mechanisms and to explore the full potential of HRV analysis to optimize medical care for ACHDs.
CRIS-Team Scopus Importer:2024-04-19
Keywords: ACHD; adults with congenital heart disease; arterial switch; atrial switch; cardiac surgery; complete transposition of the great arteries; cyanotic congenital heart defects; heart rate variability; Rastelli operation

Left Atrial Appendage Occlusion on a Beating Heart during Minimally Invasive Valve Surgery Using an Aortic Endoclamp: A Case Report - Suleiman, Mathieu; Kaemmerer, Ann-Sophie; Fechner, Jörg; Nooh, Ehab; Weyand, Michael; Heim, Christian (Journal of Clinical Medicine, 2023)
Concomitant LAA occlusion has been shown to be an effective and safe treatment for patients with atrial fibrillation during cardiac surgery to prevent embolic stroke. Minimally invasive procedures are challenging due to restricted access to and visibility of the surgical site. Also, aortic endoclamping has been developed as an alternative surgical approach to exoclamping. The aim of this article is to demonstrate the method of beating heart LAA occlusion with the Atriclip® (AtriCure, Mason, OH, USA) device during minimally invasive mitral valve surgery while using the endoclamping alternative for aortic cross-clamping.
CRIS-Team Scopus Importer:2023-10-20
Keywords: AtriClip; IntraClude Device; minimally invasive surgery; mitral valve prolapse; mitral valve replacement

Long-term course of pulmonary arterial hypertension in adults with congenital heart disease under targeted therapy: a retrospective analysis of a single tertiary center - Strack, Katharina; Freilinger, Sebastian; Busse, Amely J.; Ewert, Peter; Hauser, Michael; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Nagdyman, Nicole; Schopen, Judith; Kaemmerer, Harald; Von Scheidt, Fabian (Cardiovascular Diagnosis and Therapy, 2022)
Background: Pulmonary arterial hypertension (PAH), a common complication in adults with congenital heart disease (CHD), leads to significant morbidity and mortality. Targeted PAH medication is available, but PAH-CHD patient data are limited. Several questions regarding indication, treatment escalation, and combination therapy remain unanswered. The aim of this study was therefore to evaluate PAH-specific treatment in adults with PAH-CHD to better understand PAH-specific therapy management.Methods: In this cross-sectional study we retrospectively examined clinical, demographic, and cardiac-catheterization data and medical management for PAH-CHD, and analyzed clinical course and midterm outcome.Results: Over up to 14 years (median, 6.2 years), 103 PAH-CHD patients (66% female) receiving targeted PAH-therapy for pre-tricuspid-shunt (15.5%), post-tricuspid-shunt (32.0%), and complex CHD (52.4%) were followed. Based on modified clinical European Society of Cardiology (ESC) classification, patients were assigned to the following subgroups: Eisenmenger syndrome (ES) (45.6%), severe pulmonary vascular disease (PVD) in complex CHD (20.4%), post-repair patients (19.4%), prevalent systemic-to-pulmonary shunt (3.9%), coincidental/small defects (0%), and Fontan circulation (10.7%). Changes in targeted PAH therapy were observed 249 times, with up to 6 (median, 2) therapy changes over a median period of 1.3 years. Over the study course, the medical treatment strategy changed towards combination therapy (baseline, 13.6%; study-end, 41%), resulting mostly in stabilized functional class or even improvement in cases of prevalent systemic-to-pulmonary shunt, ES, and patients with repaired CHD. Functional class deterioration, however, was seen in patients with severe PVD due to complex CHD, and Fontan patients. Of the 103 patients in the study, 25 died (24.3%). Patients with repaired CHD and patients with systemic-to-pulmonary shunt or ES showed the best survival rates. Mortality was remarkably higher in patients with severe PVD in complex CHD and Fontan patients. Conclusions: Many patients with PAH-CHD benefited from targeted PAH therapy over a median period of 6.2 years. Treatment decisions after targeted PAH-medication initiation were based mainly on clinical assessment. To counteract disease progression, an escalation towards combination therapy was observed during the study course. We consider survival rates under targeted PAH medication to be favorable, particularly in the ES subgroup. Nevertheless, further research is needed to optimize the use of PAH medication, especially in patients with complex CHD.
CRIS-Team WoS Importer:2022-10-14

PATHFINDER-CHD: prospective registry on adults with congenital heart disease, abnormal ventricular function, and/or heart failure as a foundation for establishing rehabilitative, prehabilitative, preventive, and health-promoting measures: rationale, aims, design and methods - Freilinger, Sebastian; Kaemmerer, Harald; Pittrow, Robert D.; Achenbach, Stephan; Baldus, Stefan; Dewald, Oliver; Ewert, Peter; Freiberger, Annika; Gorenflo, Matthias; Harig, Frank; Hohmann, Christopher; Holdenrieder, Stefan; et al. (Bmc Cardiovascular Disorders, 2024)
Background: Adults with congenital heart defects (ACHD) globally constitute a notably medically underserved patient population. Despite therapeutic advancements, these individuals often confront substantial physical and psychosocial residua or sequelae, requiring specialized, integrative cardiological care throughout their lifespan. Heart failure (HF) is a critical challenge in this population, markedly impacting morbidity and mortality. Aims: The primary aim of this study is to establish a comprehensive, prospective registry to enhance understanding and management of HF in ACHD. Named PATHFINDER-CHD, this registry aims to establish foundational data for treatment strategies as well as the development of rehabilitative, prehabilitative, preventive, and health-promoting interventions, ultimately aiming to mitigate the elevated morbidity and mortality rates associated with congenital heart defects (CHD). Methods: This multicenter survey will be conducted across various German university facilities with expertise in ACHD. Data collection will encompass real-world treatment scenarios and clinical trajectories in ACHD with manifest HF or at risk for its development, including those undergoing medical or interventional cardiac therapies, cardiac surgery, inclusive of pacemaker or ICD implantation, resynchronization therapy, assist devices, and those on solid organ transplantation. Design: The study adopts an observational, exploratory design, prospectively gathering data from participating centers, with a focus on patient management and outcomes. The study is non-confirmatory, aiming to accumulate a broad spectrum of data to inform future hypotheses and studies. Processes: Regular follow-ups will be conducted, systematically collecting data during routine clinical visits or hospital admissions, encompassing alterations in therapy or CHD-related complications, with visit schedules tailored to individual clinical needs. Assessments: Baseline assessments and regular follow-ups will entail comprehensive assessments of medical history, ongoing treatments, and outcomes, with a focus on HF symptoms, cardiac function, and overall health status. Discussion of the design: The design of the PATHFINDER-CHD Registry is tailored to capture a wide range of data, prioritizing real-world HF management in ACHD. Its prospective nature facilitates longitudinal data acquisition, pivotal for comprehending for disease progression and treatment impacts. Conclusion: The PATHFINDER-CHD Registry is poised to offer valuable insights into HF management in ACHD, bridging current knowledge gaps, enhancing patient care, and shaping future research endeavors in this domain.
CRIS-Team Scopus Importer:2024-04-05
Keywords: ACHD; Adult congenital heart disease; Congenital heart defects; Heart failure; Patient outcomes; Prospective registry

Pericardial tamponade, a diagnostic chameleon: from the historical perspectives to contemporary management - Kaemmerer, Ann-Sophie; Alkhalaileh, Khaleel; Suleiman, Mathieu; Kopp, Markus; Hauer, Christine; May, Matthias; Uder, Michael; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: Pericardial tamponade (PT) early after cardiac surgery is a challenging clinical entity, not infrequently misrecognized and often only detected late in its course. Because the clinical signs of pericardial tamponade can be very unspecific, a high degree of initial suspicion is required to establish the diagnosis. In addition to clinical examination the deployment of imaging techniques is almost always mandatory in order to avoid delays in diagnosis and to initiate any necessary interventions, such as pericardiocentesis or direct cardiac surgical interventions. After a brief overview of how knowledge of PT has developed throughout history, we report on an atypical life-threatening cardiac tamponade after cardiac surgery. A 74-year-old woman was admitted for elective biological aortic valve replacement and aorto-coronary-bypass grafting (left internal mammary artery to left anterior descending artery, single vein graft to right coronary artery). On the 10th postoperative day, the patient unexpectedly deteriorated. She rapidly developed epigastric pain radiating to the left upper abdomen, and features of low peripheral perfusion and shock. There were no clear signs of pericardial tamponade either clinically or echocardiographically. Therefore, for further differential diagnosis, a contrast-enhanced computed tomography scan was performed under clinical suspicion of acute abdomen. Unexpectedly, active bleeding distally from the right coronary anastomosis was revealed. While the patient was prepared for operative revision, she needed cardiopulmonary resuscitation, which was successful. Intraoperatively, the source of bleeding was located and surgically relieved. The subsequent postoperative course was uneventful. Conclusions: In the first days after cardiac surgery, the occurrence of life-threatening situations, such as cardiac tamponade, must be expected. Especially if the symptoms are atypical, the entire diagnostic armamentarium must be applied to identify the origin of the complaints, which may be cardiac, but also non-cardiac. Central message: A high level of suspicion, immediate diagnostic confirmation, and rapid treatment are required to recognize and successfully treat such an emergency (Fig. 5). Perspective: Pericardial tamponade should always be considered as a complication of cardiac surgery, even when symptoms are atypical. The full range of diagnostic tools must be used to identify the origin of the complaints, which may be cardiac, but also non-cardiac (Fig. 5).
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cardiac tamponade; Diagnostics; Historical aspects; Pericardial effusion; Postoperative complication

Pulmonale Hypertonie bei Erwachsenen mit angeborenen Herzfehlern im Lichte der 2022-ESC-PAH-Leitlinien - Kaemmerer, Harald; Diller, Gerhard Paul; Achenbach, Stephan; Dähnert, Ingo; Eichstaedt, Christina A.; Eicken, Andreas; Freiberger, Annika; Freilinger, Sebastian; Geiger, Ralf; Gorenflo, Matthias; Grünig, Ekkehard; Hager, Alfred; et al. (Pneumologie, 2024)
The number of adults with congenital heart defects (CHD) is steadily rising and amounts to approximately 360,000 in Germany. CHD is often associated with pulmonary hypertension (PH), which may develop early in untreated CHD. Despite timely treatment of CHD, PH not infrequently persists or recurs in older age and is associated with significant morbidity and mortality. The revised European Society of Cardiology/European Respiratory Society 2022 guidelines for the diagnosis and treatment of PH represent a significant contribution to the optimized care of those affected. However, the topic of "adults with congenital heart disease"is addressed only relatively superficial in these guidelines. Therefore, in the present article, this topic is commented in detail from the perspective of congenital cardiology.
CRIS-Team Scopus Importer:2024-06-14
Keywords: angeborene Herzfehler; Eisenmenger-Syndrom; pulmonalarterielle Hypertonie

Pulmonary arterial hypertension in congenital heart disease - Part I Pulmonale arterielle Hypertonie bei Erwachsenen mit angeborenen Herzfehlern – Teil I - Kaemmerer, Harald; Diller, Gerhard Paul; Dähnert, Ingo; Eichstaedt, Christina A.; Eicken, Andreas; Freiberger, Annika; Freilinger, Sebastian; Geiger, Ralf; Gorenflo, Matthias; Grünig, Ekkehard; Hager, Alfred; Herberg, Ulrike; et al. (Pneumologie, 2023)
The number of adults with congenital heart disease (CHD) is steadily rising and amounts to approximately 360,000 in Germany. CHD is often associated with pulmonary arterial hypertension (PAH), which may develop early in untreated CHD. Despite timely treatment of CHD, PAH often persists or recurs in older age and is associated with significant morbidity and mortality.The revised European Society of Cardiology/European Respiratory Society 2022 guidelines for the diagnosis and treatment of PH represent a significant contribution to the optimized care of those affected. However, the topic of "adults with congenital heart defects" is addressed only relatively superficially in these guidelines. Therefore, this article addresses the perspective of congenital cardiology in greater depth.
CRIS-Team Scopus Importer:2023-12-08

Pulmonary hypertension in adults with congenital heart defects (ACHDs)—in light of the 2022 ESC PAH guidelines—part I: definition, epidemiology, classification, diagnostics, genetics, risk stratification and follow-up, gender aspects - Kaemmerer, Harald; Diller, Gerhard Paul; Dähnert, Ingo; Achenbach, Stephan; Eichstaedt, Christina A.; Eicken, Andreas; Freiberger, Annika; Freilinger, Sebastian; Geiger, Ralf; Gorenflo, Matthias; Grünig, Ekkehard; Hager, Alfred; et al. (Cardiovascular Diagnosis and Therapy, 2024)
The number of adults with congenital heart defects (ACHDs) is steadily increasing and is about 360,000 in Germany. Congenital heart defect (CHD) is often associated with pulmonary hypertension (PH), which sometimes develops early in untreated CHD. Despite timely treatment of CHD, PH not infrequently persists, redevelops in older age, and is associated with significant morbidity and lethality. The revised European Society of Cardiology (ESC)/European Respiratory Society (ERS) 2022 guidelines for the diagnosis and treatment of PH represent a significant contribution to the optimized care of those affected. However, the topic of “adults with congenital heart defects” is treated only relatively superficially in this context. In the present article, part I, therefore, this topic is commented on in detail from the perspective of congenital cardiology with a special focus on definition, epidemiology, classification, diagnostics, genetics, risk stratification and follow-up and gender aspects of PH in ACHDs. This paper consists of two parts. Part II will provide comments on the topics of supportive therapy, special situations like pregnancy, contraception, and non-cardiac surgery, targeted pharmacotherapy, organ transplantation, special management like shunt lesion, left ventricular disease, and univentricular hearts, interventions, intensive care, ACHDs follow-up and future perspective on PH in ACHDs. By examining these aspects in detail, this article aims to fill the gaps in the existing guidelines and provide a more thorough understanding from the perspective of congenital cardiology.
CRIS-Team Scopus Importer:2024-11-08
Keywords: congenital heart disease; Eisenmenger syndrome; Pulmonary arterial hypertension (PAH)

Pulmonary hypertension in adults with congenital heart defects (ACHDs) in light of the 2022 ESC PAH guidelines—part II: supportive therapy, special situations (pregnancy, contraception, non-cardiac surgery), targeted pharmacotherapy, organ transplantation, special management (shunt lesion, left ventricular disease, univentricular hearts), interventions, intensive care, ACHD follow-up, future perspective - Kaemmerer, Harald; Diller, Gerhard Paul; Dähnert, Ingo; Achenbach, Stephan; Eichstaedt, Christina A.; Eicken, Andreas; Freiberger, Annika; Freilinger, Sebastian; Geiger, Ralf; Gorenflo, Matthias; Grünig, Ekkehard; Hager, Alfred; et al. (Cardiovascular Diagnosis and Therapy, 2024)
The number of adults with congenital heart defects (ACHDs) is steadily increasing and is about 360,000 in Germany. Congenital heart defect (CHD) is often associated with pulmonary hypertension (PH), which sometimes develops early in untreated CHD. Despite timely treatment of CHD, PH not infrequently persists, redevelops in older age, and is associated with significant morbidity and mortality. The revised European Society of Cardiology (ESC)/European Respiratory Society (ERS) 2022 guidelines for the diagnosis and treatment of PH represent a significant contribution to the optimized care of those affected. However, the topic of “adults with congenital heart defects” is treated only relatively superficially in this context. After the first part commenting on a broad range of topics like definition, epidemiology, classification, diagnostics, genetics, risk stratification and follow-up, and gender aspects, the second part focuses on supportive therapy, special situations (pregnancy, contraception, non-cardiac surgery), targeted pharmacotherapy, organ transplantation, special management [shunt lesion, left ventricular (LV) disease, univentricular hearts], interventions, intensive care, ACHD follow-up, and future perspective. In the present article, therefore, this topic is commented on from the perspective of congenital cardiology. By examining these aspects in detail, this article aims to fill the gaps in the existing guidelines and provide a more thorough understanding from the perspective of congenital cardiology.
CRIS-Team Scopus Importer:2024-11-08
Keywords: congenital heart defect (CHD); Eisenmenger syndrome (ES); Pulmonary arterial hypertension (PAH)

Rare Case Report: Left Atrial Sarcoma Obstructing the Left Ventricular Inflow - Kaemmerer, Ann-Sophie; Suleiman, Mathieu; Agaimy, Abbas; Harig, Frank; Weyand, Michael; Tandler, Rene (Journal of Clinical Medicine, 2023)
Malignant cardiac tumors of the heart are extremely rare and may present tremendous diagnostic and therapeutic challenges. These tumors are able to infiltrate the heart and metastasize systemically. Early detection is often elusive as the clinical presentation is highly variable, posing significant diagnostic and therapeutic difficulties. Despite a multidisciplinary approach, the prognosis for patients with malignant cardiac tumors remains guarded. Early diagnosis and a multidisciplinary approach involving cardiac surgeons, oncologists and critical care specialists are crucial in the management of this disease. Further research is needed to better understand the pathomechanisms of tumor-related complications and to develop effective treatment strategies to improve patient outcomes. The rare case of a 78-year-old woman with left atrial tumor requiring emergency surgery for acutely developing mitral valve obstruction is presented. Pathology confirmed an undifferentiated pleomorphic sarcoma. This patient tragically did not survive, highlighting the difficulties of managing such a rare and deceptive heart disease.
CRIS-Team Scopus Importer:2023-11-10
Keywords: cardiac sarcoma; cardiac surgery; left atrial tumor; malignant cardiac tumor; undifferentiated pleomorphic cardiac sarcoma

The relation of aortic dimensions and obesity in adults with Marfan or Loeys-Dietz syndrome - Suleiman, Mathieu; Freilinger, Sebastian; Meierhofer, Christian; May, Matthias; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Marwan, Mohamed; Nagdyman, Nicole; Roth, Jan-Peter; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background: Aortic aneurysm and aortic dissection can have a major impact on the life expectancy of Marfan syndrome (MFS) or Loeys-Dietz syndrome (LDS) patients. Although obesity can influence the development of aortic complications, evidence on whether obesity influences the development of aortic aneurysm or dissection in MFS and LDS is limited. The aim of the present study was to elucidate the relationship between aortic size and body composition, assessed by modern bioelectrical impedance analysis (BIA) in MFS/LDS-patients.Methods: In this exploratory cross-sectional study in MFS or LDS patients, enrolled between June 2020 and May 2022, 34 patients received modern BIA and magnetic resonance imaging (MRI) (n=32) or computed tomography (CT) imaging (n=2) of the entire aorta. A P value of <0.05 was considered significant.Results: Fifty-one patients (66% female; mean age: 37.7 +/- 11.7; range, 17-68 years) with MFS or LDS were enrolled; 34 patients, 27 with MFS and 7 with LDS, underwent aortic MRI or CT scanning. The mean aortic length was 503.7 +/- 58.7 mm, and the mean thoracic aortic length and abdominal aortic length were 351.5 +/- 52.4 and 152.2 +/- 27.4 mm, respectively. The aortic bulb and the ascending aorta were measured only in the non-surgically repaired patients. Fifteen MFS (88.2%) and two LDS (40.0%) patients had an aortic aneurysm. In these, the aortic bulb tended to be larger in MFS than in LDS patients [42.6x41.9x41.2 vs. 37.8x37.4x36.8 mm; P=0.07 (-1.1; 9.1); P=0.07 (-1.2; 8.4); P=0.07 (-1.5; 7.9)]. BIA revealed mean body fat levels of 31.6%+/- 8.7% (range, 9.5-53.5%), indicating that 18 patients (52.9%) were obese. There was a significant correlation between body fat content and thoracic aortic length (R=-0.377; P=0.02), muscle mass and total aortic length (R=0.359; P=0.03), thoracic aortic length (R=0.399; P=0.02), extracellular mass (ECM), and total aortic length (R=0.354; P=0.04) , connective tissue and aortic diameters at the aortic arch (R=0.511; P=0.002), aortic isthmus (R=0.565; P<0.001), and abdominal aorta (R=0.486; P=0.004). Older age was correlated with wider aortic arch, isthmus, and abdominal aorta. Male patients had a longer aorta.Conclusions: While a slender habitus is commonly known for MFS and LDS patients, our data show that many MFS and LDS patients (especially female) do not fit this phenotypic characteristic and are obese, which is associated with a more severe aortic phenotype. This topic should be included in the clinical assessment of affected MFS and LDS patients, in addition to measurement of the aortic diameters. Physicians should systematically screen MFS and LDS patients for obesity, educate them about the potential risk of resulting aortic complications, and encourage them to adopt a healthy lifestyle, that includes (mild) exercise and a balanced diet.
CRIS-Team WoS Importer:2023-02-03
Keywords: Adults with connective tissue disease; Marfan syndrome (MFS); Loeys-Dietz syndrome (LDS); body composition; obesity

Treatment of advanced heart failure in adults with congenital heart disease: a narrative review and clinical cases - Sinning, Christoph; Huntgeburth, Michael; Fukushima, Norihide; Tompkins, Rose; Huh, June; Tataneo, Shigeru; Diller, Gerhard-Paul; Chen, Yih-Sharng; Zengin, Elvin; Magnussen, Christina; Kaemmerer, Ann-Sophie; Cho, Yang Hyun; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background and Objective: The number of adults with congenital heart disease (ACHD) is increasing worldwide. Almost all congenital cardiac lesions can be successfully treated due to the progress in neonatal surgery and pediatric cardiology with a high likelihood of surviving until adulthood. However, ACHD frequently develop sequelae related to the initial cardiac anomaly. Heart failure (HF) is one of the most common complications associated with a high morbidity and mortality.Methods: The authors did search the PubMed database regarding relevant content covering publications up to March 2022. Relevant manuscripts were classified according to the impact factor of the journal, being a guideline manuscript, a position paper by a society or a comprehensive review of the current literature. Key content and findings: Optimal HF treatment remains an unmet need in ACHD. In particular, advanced HF therapy with cardiac resynchronization therapy, ventricular assist devices or organ transplantation is still very different and more specific in ACHD compared to non-ACHD. This review aims to compile international views and evidence from the literatures on the treatment of advanced HF in ACHD. Current challenges, but also the success of different treatment strategies in ACHD are illustrated by clinical cases.Conclusions: The main finding of the review is that data is still scarce regarding ACHD with advanced HF and international efforts to collect data regarding these patients needed to improve the current standard of care.
CRIS-Team WoS Importer:2022-10-21